The effects induced by swimming training on rats submitted to normal and hypercaloric diets - Alice Cristina Antonio dos Santos; Marcelo Papoti; Fúlvia De Barros Manchado Gobatto; Mariana Rotta Bonfim; Robson Chacon Castoldi; Regina Celi Trindade Camargo; José Carlos Silva Camargo Filho (Desafio Singular, 2015)
The main aim of the present study was to analyse the effects induced by six weeks of swimming periodized training (SPT) on the aerobic capacity (AC) and body weight (BW), on rats fed with either normal or hypercaloric diets. Twenty-four Wistar rats (90 days old) were divided in two groups: Normocaloric (NG, n = 12) and Hypercaloric (HG, n = 12). The rats were fed with respective diets (NG or HG) for eight weeks and then underwent SPT for six weeks. Before (pre) and after (post) the SPT, the animals were submitted to an AC determination, using a "Chassain Test" . There was no significant changes to AC in the HG group (pre = 5.59 ± 4.56% BW vs. post = 4.45 ± 1.66% BW), but in the NG group it increased significantly (pre = 3.95 ± 2.42% BW vs. post = 4.48 ± 1.18% BW).